Development of Student Worksheets Based on RME to Improve Creative Thinking of Grade VII Middle School Students in Indonesia - Hidayati, Balu; Suparman, S (Universitas Muhammadiyah Surakarta, 2018)
Creative thinking is one of the 21st century skills that students must possess in the 2013 curriculum. Learning resources that do not integrate creative thinking skills can hinder students in learning objectives. This study has three objectives. The first objective is to analyze the needs of teaching materials that are in line with student characteristics, curriculum and subject matter. The second objective is to design RME-based teaching materials that can improve creative thinking skills. The third objective is to develop and validate teaching materials that have been previously designed. The method used in this study is the 4D model which consists of defining, designing, developing and distributing. The subjects of this study were teachers and students in junior high school grade VII. Data collection instruments consisted of questionnaires, interview guidelines, and validation sheets. Data analysis techniques use Miles and Huberman. This study provides several results. First, existing student worksheets are in accordance with textbooks, students lack focus if only using textbooks, existing student worksheets are not easy to understand, teaching materials have not been able to increase students ‘creativity, students need teaching resources that can enhance students’ creativity with examples of questions related to real life. Second, student worksheets are designed according to the RME learning model. Third, RME-based student worksheets are developed to enhance student creativity. This study concludes that the RME-based student worksheets developed are in accordance with student characteristics and curriculum. Student worksheets have been validated so they are suitable to be used to develop students’ creative thinking skills.